Web-Based Inquiry in Science Learning: Bibliometric Analysis - Dewi, Pramita Sylvia; Widodo, Ari; Rochintaniawati, Diana; Prima, Eka Cahya (Indonesian Journal of Science and Mathematics Education, 2021)
Web-based inquiry is an intermediary medium that supports broad sharing of data and ideas, in visualizing, analyzing, and offering knowledge integration. This study aims to analyze the scope of scientific research related to web-based inquiry using bibliometric studies starting from the last 10 years. Database information is obtained from Scopus indexed papers, via the Publish or Perish application. Based on the search and selection results, 65 articles were obtained which were then reviewed with Zotero and processed with the VOS viewer. The analysis used is based on the title area, according to web-based inquiry in supporting science education research. Overall, this study provides information regarding research opportunities in science learning with web-based inquiry, especially during this pandemic. This research also illustrates the publication opportunities in various countries that have a high interest in the topic of inquiry. The mapping of the bibliometric results also supports the scientific explanation between the theory and the evidence of probability. Therefore, the literature is expected to be a reference for further science research.